DESKRIPSI MANAJEMEN KESISWAAN DI SMA SWADHIPA NATAR - Yus Septika Wijaya (Faculty of Arts and Education, 2021)
This article aims to describe student management in students at Swadhipa Natar High School, and the important role of student management on student achievement. The method used in this study is a qualitative descriptive method. Data collection techniques were carried out through observation and interviews. The research subjects selected in this study were vice principals and teachers. Student management occupies a strategic position, because the central education service is focused on students and also plays a role as one of the substances of education management. One of the most important roles for the sustainability of school development and student management is school management.